APPLICATION OF NPK 15-10-12 FERTILIZER TO INCREASE THE YIELD OF PADDY FIELD, FERTILIZATION EFFICIENCY, AND EFFECTIVITY OF FERTILIZING IN INCEPTISOL - Antonius Kasno; Kiki Zakiah; I Wayan Suastika (Agric, 2022)
The quality and effective fertilizers support site-specific nutrient management of paddy fields, which can increase yields and efficiency of fertilizer. Fertilizer formulas should be based on soil nutrient status and crop requirements. This study aims to examine the reformulation of compound NPK fertilizers for lowland rice. The study was conducted in Cibungbulang, Bogor Regency from October 2020 - March 2021. The experimental design was carried out using a randomized complete block design with 10 treatments, and 3 replications. The treatments consisted of five levels of NPK 15-10-12 fertilizer doses, plus control treatment, NPK 15-15-15 and single NPK as standard, and additional treatment with the addition of straw compost. The plots were made measuring 5 m x 5 m. The results showed that statistically, the application of NPK 15-10-12 fertilizer gave the same effect on plant height, the number of tillers, weight of dry grain harvested, the weight of dry milled grain, and weight of dry straw compared to single NPK fertilizer and NPK 15-15-15. The optimum dose of NPK 15-10-12 fertilizer for lowland rice is 220 kg ha-1 combined with Urea at a dose of 225 kg ha-1. At the same dose (300 kg ha-1) the efficiency of NPK 15-10-12 fertilizer (9.70 kg grain kg-1 fertilizer) was higher than NPK 15-15-15 fertilizer (8.47 kg grain kg-1 fertilizer). Higher efficiency is indicated by lower fertilization doses. The RAE value of NPK 15-10-12 (142%) was higher than that of NPK 15-15-15 at the same dose and single NPK. This research implies that the formula for compound NPK 15-10-12 fertilizer can be used as a substitute for compound NPK 15-15-15 fertilizer.